2022
DOI: 10.1002/dmrr.3522
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum selenium level and gestational diabetes mellitus: A systematic review and meta‐analysis

Abstract: Background:The relationship between serum selenium level and gestational diabetes mellitus (GDM) is controversial. The purpose is to update and summarize previous studies to understand the relationship in more detail.Methods: PubMed, The Cochrane Library, EMBASE, Web of science, CNKI, WAN-FANG DATA and Cqvip were searched for studies published up to 3 September 2021. The random-effects model was used to measure the combined estimation.The overall effect was reported in a standard mean difference (SMD) and 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Compared with the previous research, we have the following innovations: Firstly, our research has developed clearer inclusion and exclusion criteria. Different from the research of Xu et al ( 21 ), we exclude some studies that do not meet the inclusion criteria, and the results are more convincing. For example, in the paper published by Al-Saleh et al ( 41 ) in 2005, the subjects of their study were women with insulin-dependent diabetes before pregnancy, not pregnant women with GDM, so this study was not included in our research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the previous research, we have the following innovations: Firstly, our research has developed clearer inclusion and exclusion criteria. Different from the research of Xu et al ( 21 ), we exclude some studies that do not meet the inclusion criteria, and the results are more convincing. For example, in the paper published by Al-Saleh et al ( 41 ) in 2005, the subjects of their study were women with insulin-dependent diabetes before pregnancy, not pregnant women with GDM, so this study was not included in our research.…”
Section: Discussionmentioning
confidence: 99%
“…We have made amendments to this and made further analysis according to the type of study. In addition, we conducted subgroup analyses from different perspectives not involved in previous studies ( 19 21 ), such as study type, study completion time, GDM diagnostic criteria, blood selenium measurement methods, quality of included studies, and study sample size, to further explore the source of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, increasing attention has been paid to the selenium status in patients with various cardiometabolic diseases and the association between selenium status and mortality risk of various cardiometabolic diseases. Several meta-analyses have indicated that individuals with cardiometabolic diseases tend to have lower selenium levels than healthy individuals [50][51][52], and that selenium levels are negatively associated with mortality among patients with MS, T2DM, and CVD [53][54][55]. Alterations in the metabolism of glucose and lipids characterize metabolic disorders [56].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum levels of Se-binding protein 1, an autoantibody produced by the ovary, has been reported in women with unexplained intertility and premature ovarian failure ( 1 , 10 ). In women with gestational diabetes mellitus, serum Se levels were low, and Se supplementation improved glycemic status and lipid profiles ( 11 , 12 ).…”
Section: Selenium In the Female Reproductive Tractmentioning
confidence: 99%